Investigation of an Interior Micro Permanent Magnet Synchronous Motor - Da-Chen Pang; Zhen-Jia Shi; Young-Ho Chang; Hua-Chih Huang; Gia-Thinh Bui (Energies, 2021)
This study describes the development of the world’s smallest interior permanent magnet synchronous motor (IPMSM) to increase the torque density of micromotors. The research evaluates the feasibility of the miniaturization of IPMSM since recent studies in this area focus on medium to large size compressor and traction motor applications. The standard-type and spoke-type IPMSM were selected for ease of micro machining. In order to surpass the performance of an inset motor of the same size used in previous research, the interior motors were designed with a different slot pole number, permanent magnet shape and rotor structure. Two types of interior motors were manufactured and tested to compare their performance. It was shown that the spoke-type interior motor had a better output torque, while the standard-type interior motor had a lower torque ripple, and both motors matched the specifications of commercially available motors. To achieve a higher torque density, the IPMSM designs increased the slot pole number from 6 slots 4 poles to 9 slots 6 poles. The torque density of the spoke-type motor was increased by 48% compared to the inset motor. The disadvantage is that the new design has a greater number of parts and smaller size, resulting in difficulties in manufacturing and assembly.